Influencia de la inteligencia espiritual sobre la satisfacción laboral de los servidores del Ministerio Público de distrito fiscal de Loreto periodo 2025 - Villacorta Mallqui, Manuel Alejandro (2025)
The objective was to highlight the influence of spiritual intelligence on the job satisfaction of employees of the Public Ministry of Loreto, period 2025. A study was carried out with a quantitative focus, explanatory level, basic and prospective type, using a correlational-causal cross-sectional experimental design, with a finite population of 500 public servants and a sample stratified of 151. The methodology employed was the survey, and used Likert scale questionnaires, validated and with reliability indices greater than 0.90. The hallazgos showed that 47% had high intelligence, 50% moderate and 3% low; Furthermore, 70% are satisfied with their work, 25% are somewhat satisfied and 5% are dissatisfied. The dimensions of spiritual intelligence, such as existential critical thinking and the production of personal meaning, influence favorably on job satisfaction, while the expansion of consciousness has no effect. The demographic profile of the server is not related to job satisfaction. The results conclude that there is a direct and positive influence of spiritual intelligence on the job satisfaction of employees of the Public Ministry of the Fiscal District of Loreto, period 2025 (rho= 0.196, p= 0.016), which means that greater spiritual intelligence, greater well-being and job satisfaction.